The Legal Effect of Diminishing State Sovereignty and Entering into Unions on the State's Ability to Conclude Treaties - Amjed Nori Alawadi (مجلة العصر للعلوم الانسانية والاجتماع, 2025)
There is no doubt that the state has the right to conclude treaties.,But the question arises regarding countries with limited sovereignty, or those that have entered into unions with others.,The most significant form of lack of sovereignty is that of dependent states.andSearchinIts inability to conclude treaties,Her legal personality was not fully established.,To keep her hand off external representation, However, practical experience has confirmed the need to consider each case individually.independentlyAs for entering into unions, the most important form is a federal union, which is permitted to conclude treaties.,It is a permanent union of different sovereign states.,The union has authority over its members and their citizens.,However, small states, or states within a federal union, do not possess the status of a state, and therefore do not have international legal personality.,Its legal personality dissolved into the federal union.,Therefore, it is unable to conclude treaties.